2007
DOI: 10.1158/1535-7163.mct-05-0386
|View full text |Cite
|
Sign up to set email alerts
|

The role of autophagy in the death of L1210 leukemia cells initiated by the new antitumor agents, XK469 and SH80

Abstract: The phenoxypropionic acid derivative 2-{4-[(7-chloro-2-quinoxalinyl)oxy]phenoxy}propionic acid (XK469) and an analogue termed 2-{4-[(7-bromo-2-quinalinyl)oxy]phenoxy}-propionic acid (SH80) can eradicate malignant cell types resistant to many common antitumor agents. Colony formation assays indicated that a 24 h exposure of L1210 cells to XK469 or SH80 inhibited clonogenic growth with CI 90 values of 10 and 13 Mmol/L, respectively. This effect was associated with G 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 44 publications
0
29
0
1
Order By: Relevance
“…Cleavage of a caspase-3/7 substrate containing the DEVD sequence and a quenched fluorophore (Molecular Probes/Invitrogen, E13184) was measured as described previously. 45 Cells were collected at specified intervals after irradiation for the assay, which was done in triplicate. A micro Lowry assay (Sigma-Aldrich, B3934, F9252) was used to estimate protein concentrations, using bovine serum albumin as the standard.…”
Section: Methodsmentioning
confidence: 99%
“…Cleavage of a caspase-3/7 substrate containing the DEVD sequence and a quenched fluorophore (Molecular Probes/Invitrogen, E13184) was measured as described previously. 45 Cells were collected at specified intervals after irradiation for the assay, which was done in triplicate. A micro Lowry assay (Sigma-Aldrich, B3934, F9252) was used to estimate protein concentrations, using bovine serum albumin as the standard.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to statins (Araki and Motojima, 2008) or the FTI lonafarnib (Pan et al, 2008) has been reported to induce autophagy in a variety of cell types. Although autophagy is generally perceived as being a prosurvival process, it has been linked to caspase-independent cell death (Bursch, 2001;Kessel et al, 2007;Scarlatti et al, 2009). The induction of autophagy is characterized by the accumulation of autophagosomes, which can be monitored by following the posttranslational addition of phosphatidylethanolamine to the cytosolic protein LC3-I to form LC3-II (Mizushima and Yoshimori, 2007).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Comparisons of autophagic proficient and deficient cell lines indicate that stress-induced autophagy often plays a prosurvival function (Debnath et al, 2005;Elliott and Reiners, 2008;Scarlatti et al, 2009). Nevertheless, numerous examples have been published in which autophagy appears to contribute to cell death by a nonapoptotic mechanism, which has been termed class II death (Bursch, 2001;Kessel et al, 2007;Scarlatti et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Upon starvation or drug stimuli, Bcl-2 can be phosphorylated by some upstream factors, for example, ERK, leading to release of Beclin-1 and induction of autophagy (19,20).…”
Section: Introductionmentioning
confidence: 99%